Efecto de la relación fruta-hierba deshidratada en las características fisicoquímicas, microbiológicas y sensoriales de una infusión filtrante - Cool Mero, Agustín Arnaldo (2024)
The purpose of this research work was to evaluate the effect of the dehydrated fruit-herb ratio on the physicochemical, microbiological and sensory characteristics of a filtering infusion. The doses of fruit were 70% and 75% and grass 15% and 20%. A bifactor arrangement A*B was used in DCA, obtaining four treatments with four replications. The variables evaluated were physicochemical (humidity and ash), microbiological (E. coli, Salmonella, Bacillus cereus and Clostridium perfringens) and sensory (odor, flavor, color and appearance). Using the non-parametric Kruskal Wallis test, it was shown that the humidity and ash parameters presented significant statistical differences in the A*B interaction. The means of the treatments reported values that do not comply with NTE 2392. However, T1 is established as the ideal fruit-grass percentage ratio. Regarding the microbiological analyzes of T1 and T4, they were in accordance with NTE 2392. The sensory evaluation determined that the T1 treatment obtained greater acceptance in all attributes by the untrained tasters. Therefore, it is concluded that the a2 level of the dehydrated fruit factor shows a greater impact on the variables studied, so it is important to control the drying operations to obtain a product that meets the permissible level established in the regulations.